Hematopoietic effects of Fufang E’jiao Jiang revealed by microbiome, metabolome and transcriptome analyses: a multi-omics strategy - Mo, Yueting; He, Xiyuan; Shi, Peixin; Ning, Yifei; Zhou, Mingmei; Cui, Hao; Zhang, Ting (Frontiers in Immunology, 2025)
IntroductionFufang E'jiao Jiang has been extensively utilized to replenish qi and nourish blood as the homology of medicine and food.MethodsWe analyzed the effects of FEJ on cyclophosphamide and acetylphenylhydrazine-induced anemia mice through gut microbiome analysis, fecal metabolomics, and transcriptome sequencing.ResultsFEJ markedly alleviated the anemia symptoms in the mice. FEJ markedly alleviated the anemia symptoms caused by cyclophosphamide and acetylphenylhydrazine induction. FEJ improved the gut microbiome imbalance by inhibiting the proliferation of harmful bacteria Turicibacter, Akkermansia and Tuzzerella. Fecal metabolomic data showed that FEJ regulated metabolic disorders in anemia mice and was probably associated with L-leucine, L-proline, glycine, phenylalanine, propanoic acid and butanoic acid. Transcriptome analysis indicated the amelioration of anemia was predominantly associated with the hematopoietic cell lineage, osteoclast formation and B cell receptor signaling pathway. According to Spearman's correlation analysis, there was a strong link between gut microbiota and hematopoietic index, metabolites and genes.DiscussionOur study supports the application of FEJ in anemia treatment.